2016
DOI: 10.1136/bmjresp-2016-000148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aclidinium bromide on cough and sputum symptoms in moderate-to-severe COPD in three phase III trials

Abstract: BackgroundCough and sputum are troublesome symptoms in chronic obstructive pulmonary disease (COPD) and are associated with adverse outcomes. The efficacy of aclidinium bromide 400 µg twice daily in patients with stable COPD has been established in two phase III studies (ACCORD COPD I and ATTAIN) and a phase IIIb active-comparator study. This analysis evaluated cough-related symptoms across these studies.MethodPatients were randomised to placebo, aclidinium 200 µg or 400 µg twice daily in ACCORD (12 weeks) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 46 publications
1
23
0
2
Order By: Relevance
“…Similar findings have been reported in other real-world studies after 12 weeks of aclidinium bromide treatment, [19][20][21] complementing the data from earlier Phase III studies. 18,26 As we expected, improvements in symptom severity were accompanied by a decrease in the number of nocturnal awakenings.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Similar findings have been reported in other real-world studies after 12 weeks of aclidinium bromide treatment, [19][20][21] complementing the data from earlier Phase III studies. 18,26 As we expected, improvements in symptom severity were accompanied by a decrease in the number of nocturnal awakenings.…”
Section: Discussionsupporting
confidence: 55%
“…10 Moreover, aclidinium-induced improvements in cough and sputum symptoms are supported by its antitussive activity, which is mediated by acid-sensing ion channels and mechanoreceptors. 26 These characteristics of aclidinium may explain why in a phase IIIb study, aclidinium, but not tiotropium, compared to placebo yielded significant reductions in the severity of night-time and individual early-morning (cough, wheeze, shortness of breath, and phlegm) symptoms, as well as an improvement in activity limitation due to COPD symptoms. 18 Improvement in symptom severity should be a priority for patients with COPD, as symptoms have been associated with disease exacerbations, as well as with daily activity impairment, physical activity and sleep impairments, anxiety, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal respiratory management includes mucolytics treating infection, and sputum clearance physiotherapy as appropriate. 74 Nonpharmacological treatments for refractory cough may include patient education on cough reflex hyper-sensitivity and the effect of repeated coughing, laryngeal hygiene and hydration, e.g. through use of nasal breathing, cough control techniques, and psychoeducation counselling.…”
Section: Coughmentioning
confidence: 99%
“…23,28, These articles related to clinical studies of pharmacotherapy for COPD, and included evaluations of shortacting muscarinic antagonists (SAMA; ipratropium), long-acting muscarinic antagonists (LAMA; aclidinium, glycopyrronium, tiotropium), short-acting β 2 -agonists (SABA; albuterol, salbutamol), long-acting β 2 -agonists (LABA; indacaterol, formoterol, salmeterol), and inhaled corticosteroids (ICS; fluticasone, budesonide), either alone or in different combinations. Eighteen articles reported on placebo-controlled studies; 17 articles showed that the tested active therapies/combinations provided statistically significant improvements in daytime symptomatology compared with placebo 23,40,42,44,[46][47][48][49][50][51]54,[56][57][58][59]61,64 and one study reported significant improvement in 24-h lung function with twice-daily LAMA/LABA compared with placebo. 65 Combinations consisting of LAMA/LABA (±ICS) tended to improve daytime symptoms more effectively than either LABA or LAMA monotherapy.…”
Section: Daytime Copd Symptoms: Impact Of Interventionsmentioning
confidence: 99%